CONSTRUCTION OF ASSESSMENT INSTRUMENTS IN THE FORM OF SELECTED RESPONSE TEST TO MEASURE THE ANALYTICAL THINKING SKILLS IN BIOLOGY LEARNING OF SENIOR HIGH SCHOOL - Wardhani, Irma Yuniar (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
The purpose of science learning is to master knowledge, understand and apply the concept of science, apply the skills of the science process and develop the attitude of science. Biology is a part of science, so to achieve the goal in the learning must be in accordance with the nature of science, namely science as a process, product, attitude, and application. Assessment of the achievement of knowledge competence is an assessment of students' intellectual/cognitive potential in biology learning, for which a valid and reliable assessment instrument is required. The assessment instrument reviewed here is a written test instrument. Written tests for measuring cognitive abilities can be distinguished into tests for measuring low-level cognitive abilities and measuring high-level cognitive abilities including analytical thinking skills. Analytical thinking skills is very important as a basis in solving problems faced by students especially in Biology learning. Therefore, teachers need to train students with problem-based learning solving and practice questions in the form of higher order thinking test. The form of higher order thinking test can be a choice test (chosen response test) that can measure analytical thinking skills in high school biology learning with respect to substantial aspects, constructs and language.